Composite paraganglioma-ganglioneuroma with atypical catecholamine profile and phenylethanolamine N-methyltransferase expression: a case report and literature review - Yuriko Sasaki; Maki Kanzawa; Masaaki Yamamoto; Keitaro Kanie; Hironori Bando; Kei Yoshino; Yushi Hirota; Katsumi Shigemura; Masato Fujisawa; Wataru Ogawa; Hidenori Fukuoka (Endocrine Journal)
Pheochromocytomas and paragangliomas (PPGLs) are rare tumors that secrete catecholamines and arise from the adrenal medulla or extra-adrenal sympathetic ganglia. These tumors secrete adrenaline and noradrenaline, but paragangliomas usually produce only noradrenaline because of the lack of phenylethanolamine N-methyltransferase (PNMT) expression. Composite paragangliomas, which are complex tumors consisting of multiple types of neuroblastic cells, are extremely rare. We present the case of a 46-year-old woman with an atypical catecholamine profile who was preoperatively diagnosed with pheochromocytoma. However, postoperative pathology revealed that the patient had an extra-adrenal paraganglioma accompanied by a ganglioneuroma, which led to the diagnosis of a composite tumor. Interestingly, PNMT is expressed in both paragangliomas and ganglioneuromas. In addition, we reviewed reported composite paragangliomas and compared their clinical features with those of composite pheochromocytomas. We also discuss various aspects of the etiology of composite paragangliomas and the mechanism by which PNMT is expressed in tumors.